Molecular aspects of glucose homeostasis in skeletal muscle - A focus on the molecular mechanisms of insulin resistance. - Carnagarin, R.; Dharmarajan, Arunasalam; Dass, Crispin (2015)
Among all the varied actions of insulin, regulation of glucose homeostasis is the most critical and intensively studied. With the availability of glucose from nutrient metabolism, insulin action in muscle results in increased glucose disposal via uptake from the circulation and storage of excess, thereby maintaining euglycemia. This major action of insulin is executed by redistribution of the glucose transporter protein, GLUT4 from intracellular storage sites to the plasma membrane and storage of glucose in the form of glycogen which also involves modulation of actin dynamics that govern trafficking of all the signal proteins of insulin signal transduction. The cellular mechanisms responsible for these trafficking events and the defects associated with insulin resistance are largely enigmatic, and this review provides a consolidated overview of the various molecular mechanisms involved in insulin-dependent glucose homeostasis in skeletal muscle, as insulin resistance at this major peripheral site impacts whole body glucose homeostasis.